Ensuring the Proportion of "NatureSociety-Human" Relationships in Forming the Ecological Culture of Future Primary Class Teachers (Eurasian Scientific Herald, 2022)
The article describes the problem of developing environmental consciousness and ecological culture among future primary school teachers. The issues of preservation of ecological material and spiritual heritage and ensuring the balance of "nature-societyhuman" relations are also considered